Applying Evidence in Practice: What We Can Learn from Healthcare - Dalrymple, Prudence (Evidence Based Library and Information Practice, 2010)
Applying research findings to practice is the foundation of evidence based practice. In healthcare, evidence-based practice depends upon the development, promulgation and application of clinical guidelines. While EBM has been enthusiastically embraced by many, gaps persist, and transmission from research to practice remains slow and uneven. The perception that EBM threatens professional autonomy accounts for some resistance but, even among practitioners who support EBM in concept, uptake of guidelines has encountered numerous barriers. A recent study of guideline implementation by residents in a tertiary care medical center provides insight into the barriers to guideline adoption, and draws parallels between the uptake of EBM in the healthcare sector and the uptake of EBLIP in the library and information field. Through increased understanding of the diffusion of evidence-based practice in one field, LIS practitioners can position themselves to avoid similar impediments.